Bioimpedance analysis predicts worsening events in outpatients with heart failure and reduced ejection fraction - Carlos Rodríguez‐López; Jorge Balaguer Germán; Ana Venegas Rodríguez; Rocío Carda Barrio; Hans Paul Gaebelt Slocker; Ana María Pello Lázaro; Marta López Castillo; Bárbara Soler Bonafont; Mónica Recio Vázquez; Mikel Taibo Urquía; María González Piña; Emilio González Parra; et al. (ESC Heart Failure)
Abstract Aims Heart failure (HF) with reduced left ventricle ejection fraction (LVEF) is an entity with poor prognosis characterized by decompensations. Bioelectrical impedance analysis (BIA) is used to assess volume overload (VO) and may be useful to identify apparently stable HF outpatients at risk of decompensation. The aim of this study is to analyse whether VO assessed by BIA is associated with worsening heart failure (WHF) in stable outpatients with HF and reduced LVEF (HFrEF). Methods and results This is a prospective single‐centre observational study. Consecutive stable HF outpatients with LVEF below 40% underwent BIA, transthoracic echocardiography, blood sampling, and physical examination and were followed up for 3 months. VO was defined as the difference between the measured weight and the dry weight assessed by BIA. Demographic, clinical, anthropometric, echocardiographic, and analytical parameters were recorded. The primary endpoint was WHF, defined by visits to the emergency department for HF or hospitalization for HF. A total of 100 patients were included. The median VO was 0.5 L (interquartile range 0–1.6 L). Eleven patients met the primary endpoint. Univariate binary logistic regression analysis showed that left ventricle filling pressures assessed by E/e′, N‐terminal pro B‐type natriuretic peptide, inferior vena cava dilatation (≥21 mm), signs of congestion, and VO were associated with the primary endpoint. Binary logistic regression multivariate analysis showed that VO was the only independent predictor for the primary endpoint (adjusted OR 2.7; 95% CI 1.30–5.63, P = 0.008). Multivariate Cox regression analysis also showed an adjusted hazard ratio (HR) for VO of 2.03; 95% CI 1.37–3.02, P < 0.001. Receiver‐operating characteristic curve analysis showed an area under the curve for VO of 0.88 (95% CI 0.79–0.97, P < 0.001) with an optimal cut‐off of 1.2 L. Conclusions VO assessed by BIA is independently associated with WHF in stable outpatients with HFrEF at 3 months.